(untitled) (Sirte University Journal of Humanities, 2024)
This study aimed to explore the nature of the relationship between sleep quality disturbances and generalized anxiety among displaced survivors of natural disasters in the city of Derna following Hurricane Daniel. The researchers adopted a mixed-method approach, combining both quantitative and qualitative methods to provide a comprehensive and accurate picture. The study utilized two primary tools: the Sleep Quality Scale and the Generalized Anxiety Scale to measure the variables. The sample included 162 displaced individuals affected by the hurricane, in addition to interviews with 30 displaced persons and 10 psychologists.The results indicated that the level of sleep quality disturbance was moderate, while the level of generalized anxiety was high among the displaced individuals. The study also revealed a positive correlation between sleep quality disturbances and generalized anxiety levels. Furthermore, the semi-structured interviews uncovered that the displaced individuals suffered from insomnia and persistent negative thoughts. One of the key recommendations made by experts in the field of psychology was that cognitive behavioral therapy (CBT) is considered an effective means to improve sleep quality and reduce generalized anxiety.